An affective personal trainer for elderly people - Rincon, J. A. (2019)
The main goal of this paper is to try to increase the comfort and well-being of older people through the employment of some kind of automated processes that simplify daily work. So, this paper presents a prototype of an affective personal robotic trainer which, together with a non-invasive sensor, allows caregivers to monitor certain physical activities in order to improve their performance. In addition, the proposed system also takes into account how the person feels during the performance of the physical exercises and thus, determine more precisely if the exercise is appropriate or not for a specific person.